Bibliography of Southern Appalachia - Ross, Charlotte T. (Appalachian State University, 1976)
This monograph represents a massive effort to assemble printed works of regional materials held by Appalachian Consortium members at various institutions in the Appalachia region during the mid-1970s. The five libraries contributing to the effort formed a committee to formalize and catalogue their research which resulted in the 13,000 entry bibliographic compendium which had grown from a small, local record of several hundred entries. The material was selectively annotated by Charlotte T. Ross, as well as cross referenced with other sources by members of the library committee. At the time of its publication, this work represented the largest bibliography on the Southern Appalachian Region.